A preoperative misdiagnosis case: report of an enormous solitary fibrous tumor at the anterior skull base - Shiqi Kong; Jingliang You; Yapeng Wang; Jingbo Yan; Sajjad Muhammad; Rui Zhang (Egyptian Journal of Neurosurgery)
Abstract Background Solitary fibrous tumor (SFT) is an uncommon spindle cell neoplasm primarily observed in the pleura. Instances of intracranial solitary fibrous tumors are exceedingly rare. Achieving accurate preoperative diagnosis remains challenging. This report aims to enhance the understanding of this rare disease, shedding light on diagnostic intricacies, and therapeutic considerations. Case presentation Herein, we present a case involving an enormous SFT situated at the anterior skull base, initially misdiagnosed as meningioma. Comprehensive scrutiny of preoperative images, intraoperative observations, pathological analyses, and subsequent treatment strategies is detailed. Conclusion Intracranial SFT, frequently misdiagnosed radiologically as meningiomas, may originate in the subarachnoid region, emphasizing the necessity of surgical resection and the potential benefit of postoperative radiotherapy to enhance treatment efficacy.